2021
DOI: 10.1099/ijsem.0.005003
|View full text |Cite
|
Sign up to set email alerts
|

Coniochaeta elegans sp. nov., Coniochaeta montana sp. nov. and Coniochaeta nivea sp. nov., three new species of endophytes with distinctive morphology and functional traits

Abstract: A growing interest in fungi that occur within symptom-less plants and lichens (endophytes) has uncovered previously uncharacterized species in diverse biomes worldwide. In many temperate and boreal forests, endophytic Coniochaeta (Sacc.) Cooke (Coniochaetaceae, Coniochaetales, Sordariomycetes, Ascomycota) are commonly isolated on standard media, but rarely are characterized. We examined 26 isolates of Coniochaeta housed at the Gilbertson Mycological Herbarium. The isolates were collected from healthy photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Examples of endophytes isolated from various bryophytes are summarized in Table 1 . Fungal endophytes are commonly isolated from mosses [ 40 , 41 , 42 , 43 , 44 ]. Neslon [ 45 ] performed an extensive study of fungal endophytes from the liverwort Marchantia polymorpha and observed the presence of at least 45 species belonging to the ascomycete classes Dothideomycetes, Leotiomycetes, Pezizomycetes, Saccharomycetes, and Sordariomycetes.…”
Section: The Bryendophytesmentioning
confidence: 99%
“…Examples of endophytes isolated from various bryophytes are summarized in Table 1 . Fungal endophytes are commonly isolated from mosses [ 40 , 41 , 42 , 43 , 44 ]. Neslon [ 45 ] performed an extensive study of fungal endophytes from the liverwort Marchantia polymorpha and observed the presence of at least 45 species belonging to the ascomycete classes Dothideomycetes, Leotiomycetes, Pezizomycetes, Saccharomycetes, and Sordariomycetes.…”
Section: The Bryendophytesmentioning
confidence: 99%
“…For the better part of a decade, closing the knowledge gap between uncultured and cultured fungi has been a focus for ecologists and taxonomists, especially those working on endophytes or mycorrhizal fungi symbiotic with plants (e.g., Arnold et al, 2021 ; Tanney & Seifert, 2018 ). Our coordinated microbiological and HTS surveys in the built environment yielded thousands of fungal strains, many of them now accessioned in culture collections.…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundance of three yeast ASVs of Coniochaeta in strawberry root decreased with increasing reused coir age. Coniochaeta endophytes of plants and lichens (Damm et al, 2010;Arnold et al, 2021a, Arnold et al, 2021b are positively associated with soil health (Huang et al, 2020).…”
mentioning
confidence: 99%